CD14+ monocytes and soluble CD14 of synovial fluid are associated with osteoarthritis progression - Ha-Reum Lee; Sunyoung Lee; In Seol Yoo; Su-Jin Yoo1; Mi-Hye Kwon; Chung-il Joung; Ji Ah Park; Seong Wook Kang; Jinhyun Kim (Archives of Rheumatology, 2022)
Objectives: This study aims to investigate the role of cluster of differentiation 14 (CD14) expressed monocytes and soluble CD14-mediated pathway in the synovial inflammation of knee osteoarthritis (OA). Patients and methods: Between May 2012 and July 2013, a total of 35 patients with knee OA (9 males, 26 females; mean age: 66.3±8.8 years; range, 52 to 79 years) were included in this cross-sectional study. Synovial fluid was obtained from knee joints of 35 OA patients. The CD14+ monocytes from synovial fluid mononuclear cells (SFMCs) were isolated using the MACS. The fibroblast-like synoviocytes (FLSs) isolated from knee joint tissue were incubated with recombinant CD14 and lipopolysaccharide (LPS) for 24 h. Cytokine profiling was performed with the Luminex® Performance Assay or magnetic bead panel kit. The expression of CD14 and CD16 was analyzed by immunohistochemistry and flow cytometry. Results: The concentration of sCD14 in synovial fluid was correlated with the interleukin-6 (IL-6) level (n=35) (ρ=0.654, p<0.001). The culture supernatants of CD14+ monocytes isolated from SFMC (n=15) showed a correlation between sCD14 and IL-6 (ρ=0.784, p=0.001), along with complement component 3 (ρ=0.756, p=0.010), IL-1b (ρ=0.652, p=0.012), and tumor necrosis factor-alpha (ρ=0.806, p=0.001). Following recombinant CD14 and LPS treatment, OA FLS synergistically enhanced the secretion of IL-6, IL-8, and matrix metalloproteinase 3 (n=3, p<0.05). In five paired-samples from identical patients, the proportions of CD14+ monocytes were significantly elevated in recurred synovial fluid compared to those in initial synovial fluid (p=0.043). When monocyte subsets were analyzed in SFMC (n=26), CD14+CD16+monocytes were abundant (p=0.019) and had higher toll-like receptor 4 expression than CD14+CD16- (p<0.001). Conclusion: Our study results suggest that CD14+ monocytes and the sCD14-mediated pathway play an important role in OA aggravation through inflammatory cytokine secretion.